The Effect of Multidisciplinary Collaborative Model on Knowledge, Self-Care, and Glycemic Control in Type 2 Diabetes Mellitus Patients at Assuyuthiyyah Hospital, Pati - Sony Factarun; Ernawati Ernawati; Yunie Armiyati (Eduvest - Journal of Universal Studies, 2024)
The incidence of diabetes mellitus patients is increasing which is followed by many problems that occur, including non-compliance in diabetes mellitus patients characterized by lack of knowledge, self-care and unstable glycemic control, the need for a multidisciplinary collaboration model to improve patient safety and professional satisfaction of caregivers. The purpose of this study was to determine the effect of the multidisciplinary collaborative model on knowledge, self-care and glycemic control of type 2 diabetes patients at Assuyuthiyyah Pati Hospital. Experimental research quantitative approach. Design quasi experiment pretest and post test with control group. The population of patients with type 2 diabetes mellitus in the inpatient room of Assuyuthiyyah Pati Hospital from January to March 2024 according to the inclusion criteria were 106 respondents. Non probability sampling technique, consecutive sampling. Data analysis wilcoxon test and mann whitney test. The results showed that the average knowledge of DM 2 patients in the intervention group before 64.64 and after 76.15, while in the control group before 59.30 and after 66.51, with an average intervention class difference of 11.51, the average self-care before the multidisciplinary collaborative model of 64.42 increased to 77,19 with an average intervention class difference of 10.77, Average DM 2 patients in the glycemic control intervention group before 175.25 and after 118.58 while in the control group before 200.51 and after 162.79, Average glycemic control before the multidisciplinary collaborative model of 175.25 decreased to 118.58 with an average intervention class difference of 56.67.